Perancangan Aplikasi Game Dalam Pengenalan Pancasila Menggunakan Adobe Flash CS6 - Cahya, Susilo Tiadi; Harahap, Syaiful Zuhri; Nasution, Marnis; Dar, Muhammad Halmi; Masrizal, Masrizal (Journal of Computer Science and Information System(JCoInS), 2020)
In this millennial era Citizenship Education is needed in order to guide children in the formation of good character, and foster the spirit of nationalism, mutual respect, tolerance, and also work together with each other, and the author made a Game application in the introduction of pancasila aims to increase the means, as well as the attention of children in knowing the basis of the Indonesian state, and increase knowledge.This Game application is designed using Adobe Flash CS6 software.